Detection of Biofilm Forming Streptococcus species from Bovine Mastitis - Parasana , D. K; Javia, B. B; Barad, D. B; Fefar, D. T; Ghodasara, S. N (Indian Journal of Veterinary Sciences and Biotechnology, 2023)
Mastitis is a common disease condition of farm animals, which causes production loss in animals and heavy economic loss to the dairy farmers. Streptococcus genus is one of the important etiological agents for mastitis. Biofilm formation by organisms leads to chronic infection due to more antibiotic resistance. The purpose of our study was to determine the ability to produce biofilm among bacteria of the genus Streptococcus isolated from bovine mastitis. In present study, micro-titer plate assay was used to detect the biofilm formation in Streptococcus isolates. Out of 98 Streptococcus isolates, 30 (30.61%) were non-biofilm former, 43 (43.87%) were weak biofilm former, 15 (15.30%) were moderate biofilm former and 10 (10.20%) were strong biofilm former.